1972
DOI: 10.1126/science.177.4043.80
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tolerance of Leukemic Mice to Arabinosyl Cytosine with Schedule Adjusted to Circadian System

Abstract: Mice (BDF(1)) inoculated with L1210 leukemia survive for a statistically significantly longer span when four courses of arabinosyl cytosine are administered at 4-day intervals-not in courses consisting of eight equal doses at 3-hour intervals, but in sinusoidally increasing and decreasing 24-hour courses, the largest amount being given at previously mapped circadian and circannual times of peak host resistance to the drug. This finding relates to the many therapeutic situations involving rhythmic, and thus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
3

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(47 citation statements)
references
References 5 publications
3
41
0
3
Order By: Relevance
“…13 This initial observation was later extended to testing the effect of timed administration of over 30 anticancer agents in mice and rats. 14 For most of them, the differences in toxicity ranged from 2-to 8-fold depending upon the time of their administration.…”
Section: Chronotherapy-beneficial But Inconvenient For Practical Applmentioning
confidence: 99%
“…13 This initial observation was later extended to testing the effect of timed administration of over 30 anticancer agents in mice and rats. 14 For most of them, the differences in toxicity ranged from 2-to 8-fold depending upon the time of their administration.…”
Section: Chronotherapy-beneficial But Inconvenient For Practical Applmentioning
confidence: 99%
“…Observations made Ͼ30 years ago demonstrated that the circadian pattern of arabinosyl cytosine administration determined both its toxicity and antitumor activity (8). More than 30 different anticancer drugs tested in mice and rats exhibit strong time-of-administration effects on drug-induced toxicity (9).…”
mentioning
confidence: 99%
“…It is well documented that the susceptibility to cancer chemotherapy shows circadian variations in laboratory animals (Haus et al, 1972;Scheving et al, 1976;Levi et al, 1982). In addition to reduced mortality due to acute toxicity, it has also been shown that an increase in tumour effect or cure rate can be obtained by timing the therapy to periods with less susceptibility of normal cells (Haus et al, 1972;Kuhl et al, 1974;Scheving et al, 1980a;Scheving et al, 1980b;Sothern et al, 1989;Roemeling & Hrushesky, 1990).…”
mentioning
confidence: 99%